Legal Implications of the Judex Facti Decision that acquits the Defendant of Fraud in an Agreement - Nurul Iin Pratiwi (Universitas Negeri Gorontalo, 2023)
This study aims to determine the legal implication of the judex facti decision that acquits the defendant of the criminal act of fraud in an agreement. The research method used is a normative legal research method using an approach law (statute approach) and the case approach (case approach).The results of this study show the legal implications of the Judex Facti decision which acquitted the accused of the crime of fraud in an agreement in Decision Number 208/Pid.B/2019/PN Gto, even though it had been decided it was a civil case and freed the defendants from criminal charges, even at the next level in Cassation Decision Number 277 K/Pid/2020 related to the request for a criminal case at the cassation level that was requested by the Public Prosecutor, the decision rejected the cassation request from the cassation applicant. Therefore, the legal implications of the Judex Facti decision that acquitted the accused of fraud in an agreement had implications for legal certainty, as well as implications for the re-submission of lawsuits from criminal to civil.Keywords: Implication; Crime; Fraud; Agreement